Determinants of postpartum anemia among women from a rural population in southern India - Rakesh PS; Gopichandran V; Jamkhandi D; Manjunath K; George K; Prasad J (Dove Medical Press, 2014)
PS Rakesh,1 Vijayaprasad Gopichandran,2 Dimple Jamkhandi,1 Krishna Manjunath,1 Kuryan George,1 Jasmin Prasad11Department of Community Health, Christian Medical College, Vellore, 2School of Public Health, SRM University, Kanchipuram District, Tamil Nadu, IndiaBackground: Even though the problem of anemia during pregnancy has been adequately emphasized, very little attention has been paid to postpartum anemia. The objective of the current study was to estimate the mean change in maternal hemoglobin from 36 weeks' gestation to 6 weeks postpartum and to identify the factors associated with anemia during the postpartum period among women in a rural development block in Tamil Nadu, India.Methods: Ninety-three pregnant women were interviewed using a structured questionnaire at 36 weeks' gestation and then at 2 and 6 weeks postpartum. Blood samples were collected from the participants at 36 weeks' gestation and at 6 weeks postpartum. Paired t-tests assessing the difference in mean hemoglobin prepartum and postpartum, univariate analysis, and multiple logistic regression to identify factors associated with postpartum anemia were done using Statistical Package for the Social Sciences version 12 for Microsoft Windows software.Results: The proportion of study subjects who were anemic (hemoglobin <11 g/dL) at 36 weeks' gestation was 26.8% and at 6 weeks postpartum was 47.3% (hemoglobin <12 g/dL). The mean hemoglobin at 36–38 weeks' gestation was 11.70±1.43 g/dL and at 6 weeks postpartum was 12.10±1.27 g/dL. Anemia at 36 weeks' gestation (odds ratio [OR] 10.47, 95% confidence interval [CI] 2.37–42.34), heavy blood loss perceived by the mother during delivery (OR 12.91, 95% CI 2.01–61.25), younger maternal age (<21 years, OR 2.45, 95% CI 1.28–23.86), and inadequate iron supplementation during the postpartum period (OR 3.53, 95% CI 1.18–11.37) were identified as significant factors associated with anemia at 6 weeks postpartum.Conclusion: Anemia during the third trimester of pregnancy, heavy bleeding perceived by the mother during delivery, younger maternal age, and inadequate iron supplementation during the postpartum period were associated with postpartum anemia.Keywords: anemia, hemoglobin, iron deficiency, postpartum